The Resilience of Aspiration: The Novelty of the Mystic Masseur - Udofia, Julia (American Journal of Humanities and Social Sciences, 2013)
<!--[if gte mso 9]> <![endif]--> Recent criticism of V. S. Naipaul's The Mystic Masseur has tended to see this writer as presenting pessimistic visions of the Caribbean man and his environment. As an artistic mediator of his locale and historical experience, the argument seems to have been that the unrelieved gloom of his circumstances, the apparent absence of any controlling moral centre makes the only logical possible realistic portraiture absurd, depressing and hopeless. However, this paper challenges this stereotyped criticism and the objective is to show that Naipaul is an optimistic reformer rather than “a prophet of doom” .Being a literary research, the work is mainly library-based. First, V.S. Naipaul’s The Mystic Masseur which is the primary text in this study has been rigorously examined and as many relevant critical works as could be found have been used to sharpen the focus of the arguments. In the end, it is found out that Naipaul is, indeed, an optimistic visionary whose vision aims to transform apparent hopelessness to hope and to point to the inevitable light at the end of the tunnel as demonstrated through the fortunes of the central character in the novel, and in the major technique – irony - employed by the writer in the work. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->